Political contributions of feminist analysis of romantic love to the behavioranalytic discussion of feelings - Zanuto, Juliany Oliveira; Laurenti, Carolina (Perspectivas em Análise do Comportamento, 2022)
Behavior Analysis explains feelings from a contextual perspective. However, this theory still fails to systematically explore the influence of gender political variables on the constitution of feelings, something accomplished by feminism throughout its critic of romantic love. This study aims to provide a political perspective on the Behavior Analysis discussion of feelings, considering the feminist analysis of romantic love. Bibliographic research was carried out, having theme-oriented feminist papers as a source. Sixteen articles were selected for the literature review. Data examination and categorization emphasized: the description of the patriarchal culture that produces romantic love; the role of institutions in the transmission and maintenance of romantic love; the effects of romantic love on the constitution of gender and gender identity for men and women; and the obfuscation of oppressive contingencies by the practices of romantic love. The existence of power disparities between genders regarding romantic relationships showcases the importance of a political discussion of feelings in Behavior Analysis, without which functional analysis may lead to practices that maintain oppressive systems in society intact.